Tourism Consumption Trends Changing and Tourism Promotion After the Outbreak of Covid-19 - Witsathit Somrak; Rathirat Khaewmesuan (Centre For Tourism Planning and Development, 2022)
The COVID-19 outbreak has caused an unprecedented health crisis, had a significant economic impact on many worldwide sectors and transformed the tourism sector to unprecedented levels. Also, create new challenges and new development paths. The main findings show that online information sources gained weight over consulting friends and relatives. Except for specialised and advisory services, a significant advance in digitisation is expected, where online platforms will displace physical travel agencies. Additionally, technologies such as applications, e-payment, online check-in/out, and artificial intelligence (AI) may play an increasingly important role in the long term. Each trip is a self-organised “traveller” who fewer purchases a journey from the tour service provider “tourist”. Natural-based tourism, such as slow tourism, eco-tourism and adventure tourism, becomes the primary tourism forms. Marketing and promotional communications in safety, flexibility and hospitality that emphasise the understanding of personal risk and epidemic prevention stimulate the interest of tourists’ “tourists’ motivation”.